Biomechanics of ankle instability. Part 2: Postural sway-reaction time relationship - Mitchell, A.; Dyson, R.; Hale, T.; Abraham, C. (Medicine & Science in Sports & Exercise, 2008)
Abstract: Purpose: To test the hypothesis that ankles with functional instability will demonstrate greater single-limb postural sway (PS) than their contralateral stable joint and stable healthy controls and to examine the relationship between single-limb postural sway and muscular reaction time to a simulated ankle sprain mechanism.